2022
DOI: 10.3390/foods11243972
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Treatment Affects Wax Composition and Maintains Storage Quality in ‘Kongxin’ Plum (Prunus salicina L. cv) during Postharvest

Abstract: Cuticular wax is an essential barrier against biological and abiotic stress and is also an important factor affecting fruit storage quality. This paper investigated the effect of melatonin treatment on cuticular wax and the storage quality of plum fruit at low temperature storage of 4 ± 1 °C. ‘Kongxin’ plum was treated with 150 μmol·L−1 melatonin, dried overnight at room temperature 25 ± 1 °C, and then stored at 4 ± 1 °C for 40 d. The microstructure of the fruit epidermis was examined after 0, 20, and 40 d of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Therefore, the firmness of plum fruit was significantly positively correlated with TSS content TA content ( Figure 7 ), which has been illustrated in grape [ 45 ] and apricot [ 50 ]. There was a negative correlation between firmness and soluble sugar content, which was consistent with the findings of Lin et al [ 26 ]. Weight loss had a negative correlation with TA content and positive correlation with the soluble sugar content, which showed that weight loss and soluble sugar increased as TA was consumed as a respiratory substrate [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, the firmness of plum fruit was significantly positively correlated with TSS content TA content ( Figure 7 ), which has been illustrated in grape [ 45 ] and apricot [ 50 ]. There was a negative correlation between firmness and soluble sugar content, which was consistent with the findings of Lin et al [ 26 ]. Weight loss had a negative correlation with TA content and positive correlation with the soluble sugar content, which showed that weight loss and soluble sugar increased as TA was consumed as a respiratory substrate [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…Cuticular wax extraction was performed using the method proposed by Lin et al [ 26 ]. Cuticular wax was extracted from three varieties of plum fruits stored for 0, 10 and 20 d. Fruits of the same shape and size ( n = 10) were selected, and each fruit was extracted in three 500 mL beakers for 30 s in turn so that all the fruits were immersed and agitated for 30 s in chloroform/methanol ( v / v : 4/1) under a fume hood, which ensured that the fruit epidermis was not damaged.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to these authors, melatonin activates the accumulation of abscisic acid and, in turn, also regulates the transport of water across the membrane and cuticle. Nije et al [ 41 ] and Lin et al [ 42 ] also observed maintenance of firmness and weight in the treated fruit due to melatonin-promoted synthesis of long-chain alkanes that were positively correlated with water retention and firmness.…”
Section: Discussionmentioning
confidence: 99%